2021
DOI: 10.1038/s41598-021-01648-x
|View full text |Cite
|
Sign up to set email alerts
|

The transition from the female-like great calls to male calls during ontogeny in southern yellow-cheeked gibbon males (Nomascus gabriellae)

Abstract: It is well known that gibbons emit a pattern of vocalizations, which is specific for species and sex. A previous study showed, however, that immature southern yellow-cheeked gibbon (Nomascus gabriellae) males produce only female-like great calls from 2.3 to 5.3 years of age in co-singing interactions with their mothers. To date, nothing is known about how the vocal repertoire of a male changes from the female-like call (great call) to the male call (staccato notes and multi-modulation phrase) during vocal onto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…This behavior has been reported in duetting gibbons such as H. lar and agile gibbons (H. agilis; Koda et al, 2014), and N. gabriellae, northern white-cheeked gibbon (Nomascus leucogenys), and black crested gibbons (Nomascus concolor; Schilling, 1984;Hradec et al, 2016Hradec et al, , 2017Hradec et al, , 2021. With physical and sexual maturation, young males of N. gabriellae transitioned from female-like songs to a mix of both male and female-like song parts, to male 10.3389/fevo.2022.910260 calls only (Hradec et al, 2021). Similar to immature female gibbons, immature males may also co-sing with their mothers to practice vocalizing.…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations
“…This behavior has been reported in duetting gibbons such as H. lar and agile gibbons (H. agilis; Koda et al, 2014), and N. gabriellae, northern white-cheeked gibbon (Nomascus leucogenys), and black crested gibbons (Nomascus concolor; Schilling, 1984;Hradec et al, 2016Hradec et al, , 2017Hradec et al, , 2021. With physical and sexual maturation, young males of N. gabriellae transitioned from female-like songs to a mix of both male and female-like song parts, to male 10.3389/fevo.2022.910260 calls only (Hradec et al, 2021). Similar to immature female gibbons, immature males may also co-sing with their mothers to practice vocalizing.…”
Section: Introductionsupporting
confidence: 54%
“…Then what could be the evolutionary function of co-singing in H. moloch male offspring? Male offspring may co-sing with their mothers to avoid competition with fathers by female-like great calls, and thus by relaying information about their immature status (Hradec et al, 2021). However, this is unlikely because in both N. gabriellae (Hradec et al, 2021) and H. moloch (present study), co-singing episodes between young males and mothers were no longer observed after 8 years of age.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Some advances have been made in singing primates, notably in Sulawesi tarsiers (genus Tarsius, Clink et al, 2020), indris (Indri indri, Torti et al, 2013), coppery titi monkeys (Plecturocebus cupreus, Lau et al, 2020), and gibbons (Geissmann, 2002). Additional studies have focused on song dynamics (e.g., rhythm, pitch, and degree of overlap) (Gamba et al, 2016), song flexibility (Clarke et al, 2006;Terleph et al, 2018a;Hradec et al, 2021a), song individuality (Sun et al, 2011;Clink et al, 2021), song ontogeny (Hauser, 1989;Pistorio et al, 2006;Hradec et al, 2017Hradec et al, , 2021bDe Gregorio et al, 2021), song recognition (Raemaekers and Raemaekers, 1985;Mitani, 1987;Caselli et al, 2015), song taxonomy, and genetic relatedness (Konrad and Geissmann, 2006;Torti et al, 2017). However, the question of whether songs by singing primates transmit information about pairing status (i.e., paired vs. unpaired individuals) has received surprisingly little attention.…”
Section: Introductionmentioning
confidence: 99%